Rapid detection and identification of methillin - resistant staphylococcus aureus (MRSA) by real-time polymerase chain reaction (RT-PCR) - Zarizal Suhaili
Meticilin-resistance Staphylococcus aureus (MRSA) has been reported as one of the major contributor of nosocomial infection in the world and ranks as one of the most difficult pathogen to treat in hospitalized patients. This study aimed to utilized molecular diagnostic techniques for the detection and identification of Staphyloccus aureus especially MRSA as well as methicillin-sensitive Staphylococcus aureus (MSSA) and subsequently to study antibiotic biograms profiles of selected isolates. Thirty-two clinical isolates of S.aureus from two teaching hospitals, University Malaya Medical Center (UMMC), Hospital University of Kebangsaan Malaysia (HUKM) and Hospital Sultanah Nur Zahirah (HSNZ), Kuala Terengganu were used in this study.The antibiogram profile of S. aureus clinical isolates from HSNZ and reference isolates from American Type Culture Collection (ATCC) was established by using agar disc diffusion method. Out of the 19 isolates from HSNZ, 11 were confirmed as MRSA which exhibitting multidrug resistance against amikacin, cefoxitin, gentamycin, clindamycin, erythromycin, fusidic acid, norfloxacin, oxacilin, penicilin, rifampin,streptomycin, tetracycline, and trimetroprim. All isolates were still susceptible to vancomycin. Apart from vancomycin, four other antibiotics used i.e.,chloramphenicol, linezolid, novobiocin, and teicoplanin seem to be the most effective antibiotic against all S. aureus isolates. Rapid molecular diagnostic by real-time PCR SYBR Green I was established. Development and verification of real-time PCR primers by in-silico PCR was established. Three selected genes as a species-specific marker coa (staphylocoaguase), nuc (thermonuclease) and mecA (methicillin-reistance) were verified against 18 selected S. aureus strains by using in-silico PCR. The actual laborotory verification, of all three selected genes were positively produced single specific melting curve analysis peak Tm qt 76.16+- 0.8 oC, 78.5 +- oC 0.4 oC and 74.41 +- 0.6 oC for coa, nuc, and mecA respectively against 32 bacterial strains including ATCC reference strains. There was no disagreement between in-silico PCR and real-time PCR. In this study a MRSA detection method based on the melting temperature analysis profilling was established. Simplex and duplex real-time PCR assay were used for the simultaneous detection of nuc (species-specific) and mecA (methicillin-resistance) genes in a single SYBR Green I real-time PCR tube assay. Evaluations were based on the melting temperature (Tm) analysis of the amplicons using 23 S. aureus clinical isolates including three ATCC S. aureus standards strains. Real-time PCR amplification products with melting peaks at 78.39 +-0.4 oC and 74.41 +- 0.6 oC were detected for nuc and mecA genes, respectively. Each real-time PCR assay was completed within two hours. This rapid genotypic method is useful for the detection of resistant determinant (mecA) and identification of S. aureus (nuc) clinical isolates.